Complementary assays helping to overcome challenges for identifying neuraminidase inhibitors. (February 2015) - Richter, Martina; Schumann, Lilia; Walther, Elisabeth; Hoffmann, Anja; Braun, Heike; Grienke, Ulrike; Rollinger, Judith M; von Grafenstein, Susanne; Liedl, Klaus R; Kirchmair, Johannes; Wutzler, Peter; Sauerbrei, Andreas; et al.
ABSTRACT : Aims : In this study, we analyze the challenges involved in detecting novel neuraminidase inhibitors (NAIs) and offer strategies to overcome them with complementary bioassays.Materials & Methods: We investigated the inhibitory activities of NAIs (oseltamivir, zanamivir, DANA, katsumadain A and remazol) as well as non-NAIs (amantadine, nucleozin and rifampicin) on influenzaviral and bacterial ( Streptococcus pneumoniae, Clostridium perfringens and Vibrio cholerae ) neuraminidases (NAs) with chemiluminescence (CL)- and fluorescence (FL)-based assays. Furthermore, hemagglutination-based NA inhibition assays were established.Results: Our study shows three types of signal interference affecting the readout of biochemical assays: self-FL (katsumadain A and remazol), FL quenching (rifampicin) and CL quenching (rifampicin, remazol, nucleozin and katsumadain A). These challenges were overcome by hemagglutination-based assays.Conclusion: The latter allow a robust performance in discriminating NAIs and non-NAIs.